Źródła finansowania zrównoważonego rozwoju obszarów wiejskich w Polsce po akcesji do Unii Europejskiej - Szydło, Wiktor (Sources of Support of Rural Development in Poland after Accession to the EU, 2006)
The article describes and analyzes spending on sustainable development in rural areas in Poland. Special attention was paid to agricultural sector. This kind of support is gradually increasing. How-ever, enlargement of the European Union does not entail any substantial increase of funds for the whole sector. The share of Common Agricultural Policy in GDP of the EU is falling from 0.61% in the year 1993 to 0.43% now and only 0.33% in 2013. An increase of spending on the second pillar of CAP will be connected with a creation of European Agricultural Fund for Rural Development which will replace present scattered and often not transparent support of rural areas. Nevertheless, the details of new support are still not known.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (12); 2006; nr 1122, s. 216-232